Altering element interactivity and variability in example‐practice sequences to enhance learning to write Chinese characters. Issue 4 (4th May 2020) - Lu, Jia; Kalyuga, Slava; Sweller, John
Summary: The isolated elements and variability effects of cognitive load theory were used to alter the element interactivity of Chinese characters when instructing novice learners (72 overseas students at a Chinese university) in writing characters using worked examples‐practice procedures. A group of characters with more than eight strokes was disassembled into three individual components. Students were required to trace examples and practice writing of either similar sequences of isolated components followed by integrated components of full characters (Isolated–Integrated sequences); variable sequences of isolated followed by integrated components (Variability–Integrated sequences); or conventional Integrated–Integrated sequences of full characters. It was hypothesized that the fully integrated stroke‐movements form of example‐practice sequences would result in less learning due to a greater cognitive load. The results demonstrated that the participants in both the Isolated–Integrated and Variable–Integrated groups performed significantly better than the Integrated–Integrated group with the Variable–Integrated group outperforming the Isolated–Integrated group.